Theory and Practice of Remote Radar Probing the Earth’s Surface - G. I. Linets; A. V. Bazhenov; N. V. Grivennaya; V. D. Goncharov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2024)
Remote assessment of the dielectric characteristics of the earth’s surface is in demand for solving various industrial tasks. The article discusses the theoretical and practical aspects of measuring the dielectric const ant of the Earth’s surface when it is irradiated with a radio signal in a two-position system from unmanned aerial vehicles. The required depth of penetration of the probing radio signal under the surface is achieved using the UHF band and oblique irradiation under conditions of complete (pseudo-complete) refraction of the electromagnetic wave at the air-surface boundary. The novelty of the proposed approach lies in the oblique irradiation of the Earth’s surface with a horizontally and vertically polarized radar signal, followed by registration of amplitudes and phase shifts of interference wave oscillations.and finding the Brewster angle by the parameters of the interference wave. The practical application of this approach is to measure the moisture content of agricultural soils and determine the strength characteristics of sea ice.